Leveraging the timing and frequency of patient decision aids in longitudinal shared decision‐making: A narrative review and applied model - Lara R. LoBrutto; Gemmae Fix; Renda S. Wiener; Amy M. Linsky (Wiley, 2022)
Abstract Introduction Shared decision‐making (SDM) is intended to increase patient‐centredness of medical decision‐making for patients with acute and chronic conditions. Concurrently, patient decision aids (PtDAs) can supplement SDM by providing information to guide communication between patients and healthcare providers. Because of the prevalence of chronic conditions, where decisions may be extended or recurring, we sought to explore how effectively these tools have been leveraged in this context. Methods We conducted a narrative review of the literature on both SDM and PtDAs, searching PubMed and Boston University's library database search tool for English‐language articles published from January 2005 until March 2021. Additional search terms focused on temporality. Drawing from our findings, we developed a combined framework to highlight areas for future research using the discussion of end‐of‐life decisions as an exemplar to illustrate its relevance to chronic care contexts. Results After screening 57 articles, we identified 25 articles that fulfilled the inclusion criteria on SDM, PtDA use and temporality for chronic care. The literature on SDM highlighted time outside of the medical visit and opportunity to include outside decision partners as important elements of the process. PtDAs were commonly evaluated for process‐related and proximal outcomes, but less often for distal outcomes. Early evidence points to the value of comparative outcome evaluation based on the timing of PtDA distribution. Conclusion Our review of the literature on SDM and PtDAs reveals less attention to the timing of PtDAs relative to that of SDM. We highlight the need for further study of timing in PtDA use to improve longitudinal SDM for chronic care. The model that we propose in our discussion provides a starting point for future research on PtDA efficacy. Patient or Public Contribution Five patient consultants provided input and feedback on the development and utility of our model.